PORT PERFORMANCE IN THE PERSPECTIVE OF SHIP ARRIVAL AND DEPARTURE REPORT DATA - Simanjuntak, Ronald; Sihombing, Derma Watty; Baihaqi; Lestari, Widianti; Zulaikah, Siti (Meteor STIP Marunda, 2024)
The seaport as a gateway to the regional, national and international economy must pay attention to the performance of operational services, including the level of service quality of ships, goods and port facilities. Activities at the port such as sea transportation operations must be reported to the Port Operator in accordance with the format of the ship arrival and departure report (LK3) which includes the type of ship, docking terminal, arrival time data and departure time from the Port. One perspective of port performance measurement is ship service which can be measured from how long the ship is at the terminal until it leaves the port. This research method uses a quantitative approach and the Data Envelopment Analysis (DEA) method. This study aims to determine the statistical approach and measure port performance, namely turnaround time and performance efficiency. The results of the study for 2022 obtained for the type of container ship, Tanjung Emas Port has a turnaround time of 23 hours while Tanjung Priok Port and Tanjung Perak Port are more than 24 hours and port performance efficiency with DEA efficient rating value Ѳ =1 at Tanjung Priok and Tanjung Perak ports.